INTERAKSI VIRTUAL DAN KETERIKATAN EMOSIONAL DI TIKTOK: STUDI KASUS FENOMENA VIRTUAL TAGAR #KABURAJADULU - Rahim, Umar Abdur; Bayu, Muhammad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The advancement of digital technology has transformed the landscape of social communication, with platforms like TikTok serving not only as entertainment spaces but also as venues for emotional expression and interaction. This study aims to explore how virtual interaction within the viral hashtag phenomenon #KaburAjaDulu fosters emotional attachment among TikTok users in Indonesia. Using a qualitative descriptive approach, this research analyzes TikTok content utilizing the hashtag and reviews academic literature on digital communication dynamics, self-disclosure, and emotional bonding in social media. The findings reveal that the #KaburAjaDulu hashtag functions as a collective outlet for self-expression, where users channel life stressors through humorous, ironic, or melancholic content. Engagement through TikTok’s interactive features—such as duet, stitch, and live comments—enhances emotional connectivity between content creators and their audiences, resulting in the formation of empathy-based communities. This phenomenon reflects key aspects of Indonesian culture, including collectivism, humor as a coping mechanism, and the inclination to seek emotional support within digital spaces. The study concludes that TikTok is more than a mere entertainment platform; it serves as a significant emotional and social outlet, particularly for the younger generation. The #KaburAjaDulu trend illustrates how Indonesia’s digital society responds to social pressures in creative, emotional, and collaborative ways.